Finding the Right Words - Di Sciacca, Claudia (University of Toronto Press, 2008)
This rigorous, well-documented volume demonstrates the significance of the Synonyma to our understanding of the literary pretensions and pedagogical practices of Anglo-Saxon England, and offers new insights into the interaction of Latin and vernacular within its literary culture.
Description based on publisher supplied metadata and other sources
Keywords: Isidor; Synonyma; Rezeption; Übersetzung; Altenglisch